2020
DOI: 10.1186/s12870-020-2264-2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and comparative proteomic analysis provides new insights into the effects of shade stress in maize (Zea mays L.)

Abstract: Background: Shade stress, a universal abiotic stress, suppresses plant growth and production seriously. However, little is known regarding the protein regulatory networks under shade stress. To better characterize the proteomic changes of maize leaves under shade stress, 60% shade (S) and supplementary lighting (L) on cloudy daylight from tasseling stage to physiological maturity stage were designed, the ambient sunlight treatment was used as control (CK). Isobaric tag for relative and absolute quantification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 51 publications
3
36
0
1
Order By: Relevance
“…In recent years, global solar radiation intensity has been declining as a result of climate change; the amount of solar radiation reaching the surface has decreased by an average of 2.7% per decade over the past 50 yr (Abakumova, Gorbarenko, Nezval, & Shilovteseva, 2008;Che et al, 2005;Stanhill & Cohen, 2001). Some maize (Zea mays L.) growing areas in China receive low solar radiation due to high cloud cover (Cui, Camberato, Jin, & Zhang, 2015;Gao, Liu, Zhao, Liu, & Zhang, 2020). Additionally, the increase in planting density leads to canopy closure and consequently reduces the amount of solar radiation reaching the bottom of the canopy, which is not conducive to biomass accumulation (Enrico et al, 2013;Mao et al, 2014;Purcell, Ball, Reaper, & Vories, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, global solar radiation intensity has been declining as a result of climate change; the amount of solar radiation reaching the surface has decreased by an average of 2.7% per decade over the past 50 yr (Abakumova, Gorbarenko, Nezval, & Shilovteseva, 2008;Che et al, 2005;Stanhill & Cohen, 2001). Some maize (Zea mays L.) growing areas in China receive low solar radiation due to high cloud cover (Cui, Camberato, Jin, & Zhang, 2015;Gao, Liu, Zhao, Liu, & Zhang, 2020). Additionally, the increase in planting density leads to canopy closure and consequently reduces the amount of solar radiation reaching the bottom of the canopy, which is not conducive to biomass accumulation (Enrico et al, 2013;Mao et al, 2014;Purcell, Ball, Reaper, & Vories, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the efficient photosynthetic rate under low-light treatments enhances the potential capacity of antioxidant enzymes. Some evidence in the literature has suggested that plants under light shading mediate some of these processes, such as increasing subunits of ferredoxin, cytochrome P450 and PS1 reaction cores, which are accompanied by increases in some metabolites (particularly carbon metabolites), and thus establish equilibrium under shading conditions that result in a low-light response [ 34 ], with no or low substantial impact on yield. Similarly, tolerant rice varieties have been shown to exhibit higher chlorophyll a and b contents and lower chlorophyll a/b ratio than the light-sensitive varieties [ 6 ], in addition to maintaining a higher capacity of antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted on maize plants, shading conditions decreased the abundance of sucrose synthases and carbohydrate substances (fructose-bisphosphate aldolase, starch synthase, and isoflavone reductase) initially by inhibiting PSI and dark reactions, thus enhancing light energy utilization by the accumulation of electron-transfer-related proteins and alleviating the detrimental effects of shading on plant physiological processes. An investigation of differentially abundant proteins (DAPs) revealed a significant increase in PSII proteins and the inhibition of starch synthesis and CO 2 fixation, which led to damaged photosynthetic apparatus and consequently reduced biomass and grain yield during late growth stages [ 34 ]. Shading has recently been reported to decrease the grain yield of fragrant rice, which has been alleviated by the exogenous application of γ-amino butyric acid (GABA) to non-protein amino acids [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…One question we aimed to address was whether the high CO 2 assimilation rates observed in soybean under shading condition is a consequence of the signi cant improvement of the photosynthetic system or the activity of the related reaction process of the Calvin-Benson cycle. Related studies have shown that C3 cycle-related enzymes are notably affected by light intensity [12,14] . As the most abundant enzyme in plants, the proportion of activated Rubisco in C3 plants is about 25% [27,28] , the content may be excessive, so the reduction of Rubisco carboxylation rate can be compensated by rapid activation.…”
Section: Discussionmentioning
confidence: 98%
“…Photosynthesis is a complex biochemical and biophysical process that comprises photosynthetic pigment synthesis, light energy electron transport, and the Calvin cycle [5,6] , these processes are all affected by the light intensity [7] . Leaf area, chlorophyll content, and antenna pigment-protein under weak light environment improve the light interception and the absorption e ciency [8,9] , but the decrease of light conversion and electron transfer e ciency [10,11] as well as a signi cant decrease in expression level and activity of photosynthetic carbon immobilized enzyme [12][13][14] resulting in the inevitable reduction of photosynthetic capacity under weak light. Increasing nutrients is one of the important ways for crops to improve the use of low light [15] .…”
Section: Introductionmentioning
confidence: 99%